2019
DOI: 10.1177/1469066719875655
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of morphine in human urine by surface-ionization mass spectrometry

Abstract: Detection and analysis of drugs-of-abuse in biological fluids are the essential tasks for the law enforcement, forensic toxicology, doping research and social health. In this work, we developed a surface-ionization mass spectrometry method for direct detection of trace amount of morphine spiked in blank urine. The mass-spectrometric analysis of spiked samples was carried out without preliminary extraction and chromatographic separation. It was found out that the major fragment ions at m/z 144, 146 could be ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
15
0
4
Order By: Relevance
“…In our previous work, urine spiked with morphine spiked was analyzed by SI/MS. 42 It was found that a major peak of the analyte in the mass spectrum could be served as an indicator line in biofluids. Other detected peaks were products of deep fragmentation of cocaine on the heated surface as well as some peaks such as with m/z 86, 112, and 126 were related to urine ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, urine spiked with morphine spiked was analyzed by SI/MS. 42 It was found that a major peak of the analyte in the mass spectrum could be served as an indicator line in biofluids. Other detected peaks were products of deep fragmentation of cocaine on the heated surface as well as some peaks such as with m/z 86, 112, and 126 were related to urine ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Along with these requirements, the emitters with the high work function for their stable operation in time and with high fluxes of organic compounds should be used as an ion source. 16 For the SI studies of organic compounds, the static magnetic, 25 time-of-flight (TOF) 26 and quadrupole 21,27 mass spectrometers are also used. The static magnetic mass spectrometers allow analysis of monomolecular decays of vibrationally excited maternal ions.…”
Section: Methodsmentioning
confidence: 99%
“…14,17 By now, a large number of organic and bioorganic compounds on emitters from various materials have been mass-spectrometrically investigated under vacuum conditions. 1821 It was found that the molecules of organic solvents (ketones, aldehydes, alcohols, simple hydrocarbons) and simple gases (H 2 , N 2 , CO 2 , CO, H 2 O) are almost not ionized by SI. The method has a high selectivity to the ionization energy of the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Как известно, важнейшими параметрами детекторов являются их чувствительность, селективность, линейно динамический диапазон (ЛДД), стабильность и быстродействие [17,[29][30][31][32][33][34]. На данный момент существует большое количество научно-практических работ, посвященных выявлению закономерностей ПИ и исследованию физико-химических свойств органических и биоорганических соединений [22][23][24][25][26][27][28], поиску эффективных и эмиссионно-стабильных ПИ эмиттеров для детекторов [35][36][37][38][39], определению чувствительности и ЛДД ПИ детекторов к веществам [17][18][19][20][21][25][26][27][28], разработке методов обнаружения и анализа веществ в различных биологических образцах на основе ПИ детекторов [40][41][42][43][44][45][46][47]. Несмотря на это, отсутствуют сведения о закономерностях быстродействия ПИ детекторов.…”
Section: Introductionunclassified